2007
DOI: 10.1542/peds.2006-1354
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Dexamethasone Therapy and Cerebral Tissue Volumes in Extremely Low Birth Weight Infants

Abstract: We identified smaller total and regional cerebral tissue volumes in extremely low birth weight infants treated with relatively conservative regimens of dexamethasone. These volume deficits may be the structural antecedents of neuromotor and cognitive abnormalities reported after postnatal dexamethasone treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 30 publications
(32 reference statements)
4
90
4
1
Order By: Relevance
“…Earlier studies showed that the corticosteroid dexamethasone, used mostly to prevent BPD, has a negative effect on brain growth and especially on cerebellar growth. 48 However, we did not find an independent effect of corticosteroid-treated BPD on the volume of any brain region. An explanation may be that in our institution hydrocortisone is used instead of dexamethasone.…”
Section: Discussioncontrasting
confidence: 73%
“…Earlier studies showed that the corticosteroid dexamethasone, used mostly to prevent BPD, has a negative effect on brain growth and especially on cerebellar growth. 48 However, we did not find an independent effect of corticosteroid-treated BPD on the volume of any brain region. An explanation may be that in our institution hydrocortisone is used instead of dexamethasone.…”
Section: Discussioncontrasting
confidence: 73%
“…Even multiple courses of antenatal GC treatment do not appear to confer significant neurodevelopmental risk at 2-3 years of age (45,54), although school-age follow-up studies are required to fully assess this issue. In contrast, many studies show that use of neonatal (i.e., postnatal) treatment with Dex leads to motor and intellectual deficits (3,4,6,20).…”
Section: Clinical Implications the Synthetic Gcs Dex And β-Methasonementioning
confidence: 98%
“…ous studies have indicated that GC treatment results in decreased cerebellar volumes in the rodent and human brain (19,20). To confirm the effects of GC treatment on early neonatal cerebellar development involving multiple courses, we treated C57BL/6J mouse pups with Dex daily for 1 week from P0 to P7 (Figure 1).…”
Section: Gc Treatment Inhibits Cerebellar Growth and Cgnp Proliferatimentioning
confidence: 99%
“…While the specific targets of the anti-inflammatory effects of corticosteroid treatment in the model remain undefined, infection-induced soluble inflammatory mediators, including tumor necrosis factor alpha (TNF-␣), gamma interferon (IFN-␥), and IFN-␤, were decreased (29). Because of the potential toxicity of corticosteroids for the developing CNS, as well as the off-target effects of corticosteroids that have been documented in clinical studies and in animal models, we sought more targeted approaches to decrease CNS inflammation in infected mice (30)(31)(32). We focused our studies on responses associated with TNF-␣ because pathway analyses of the transcriptome from cerebella of infected mice revealed that TNF-␣ represented a central node in the pathway of the observed inflammatory responses (26).…”
mentioning
confidence: 99%